Leaf‐level photosynthetic capacity in lowland Amazonian and high‐elevation Andean tropical moist forests of Peru. Issue 3 (8th July 2016) - Bahar, Nur H. A.; Ishida, F. Yoko; Weerasinghe, Lasantha K.; Guerrieri, Rossella; O'Sullivan, Odhran S.; Bloomfield, Keith J.; Asner, Gregory P.; Martin, Roberta E.; Lloyd, Jon; Malhi, Yadvinder; Phillips, Oliver L.; Meir, Patrick; et al.
Summary: We examined whether variations in photosynthetic capacity are linked to variations in the environment and/or associated leaf traits for tropical moist forests (TMFs) in the Andes/western Amazon regions of Peru. We compared photosynthetic capacity (maximal rate of carboxylation of Rubisco ( V cmax ), and the maximum rate of electron transport ( J max )), leaf mass, nitrogen (N) and phosphorus (P) per unit leaf area ( M a, Na and Pa, respectively), and chlorophyll from 210 species at 18 field sites along a 3300‐m elevation gradient. Western blots were used to quantify the abundance of the CO2 ‐fixing enzyme Rubisco. Area‐ and N‐based rates of photosynthetic capacity at 25°C were higher in upland than lowland TMFs, underpinned by greater investment of N in photosynthesis in high‐elevation trees. Soil [P] and leaf Pa were key explanatory factors for models of area‐based V cmax and J max but did not account for variations in photosynthetic N‐use efficiency. At any given Na and Pa, the fraction of N allocated to photosynthesis was higher in upland than lowland species. For a small subset of lowland TMF trees examined, a substantial fraction of Rubisco was inactive. These results highlight the importance of soil‐ and leaf‐P in defining the photosynthetic capacity of TMFs, with variations in N allocation and Rubisco activation state further influencing photosynthetic rates and N‐use efficiency of these critically important forests. Abstract : See also the Commentary on this article by McDowell & Xu, 214 : 903–904 .